Tinjauan Hukum Pidana Dalam Undang-undang Nomor 11 Tahun 2008 Tentang Informasi dan Transaksi Elektronik di Indonesia - Ivan Zairani Lisi (Jurnal Risalah Hukum, 2007)
The governmental decision to validate the Undang-undang Nomor 11 Tahun 2008 Tentang Informasi dan Transaksi Elektronik actually provides a better vision and mission. Taking account the low level effort of improving internet penetration, the government attempts to protect the national asset (youth generation) from the effect of Internet-based pornography content. Undang-undang Nomor 11 Tahun 2008 Tentang Informasi dan Transaksi Elektronik seems judged by some as less perfect or as premature to be prevailed due to its weaknesses. One of its articles shocking the virtual world will be Article 27. The article explains the prohibited conducts. More specific, Article 27 verse (1) considers the morality. Some disagree with this Act because Internet provides so much pornography content. Others feel afraid that the Act becomes a way of such opportunistic person to blackmail some Internet shops. Therefore, it needs further review on prohibited conducts in pursuant to the criminal law aspects as written in Undang-undang Nomor 11 Tahun 2008 Tentang Informasi dan Transaksi Elektronik. Key words: Tindak pidana (crime), perbuatan yang dilarang (prohibited conducts), Undang-undang Nomor 11 Tahun 2008.